The Role of Ragunan Zoo as A Wildlife Conservation Medium, 1966-1993 - Abimanyu, Akhdiat Dimas; Subekti, Slamet (Sahabat Publikasi, 2025)
This article examines the role of Ragunan Zoo as a medium for wildlife conservation from 1966 to 1993, focusing on its development amidst criticism for prioritizing tourism over conservation. Using historical methodology, the study traces the evolution of Ragunan Zoo from its origins as Planten en Dierentuin during the Dutch colonial era to its transformation into a modern conservation institution. The research highlights key efforts by Ragunan Zoo to address criticism, including the development of animal collections, breeding programs, partnerships with international zoos, and educational initiatives. The research also explores the tangible outcomes of these efforts, such as animal releases, successful breeding programs, and international recognition, including the Ramon Magsaysay Award awarded to Benjamin Galstaun, the zoo's first director. Despite challenges like limited funding and outdated infrastructure, Ragunan Zoo has made significant strides in balancing its roles as a conservation, educational, and recreational institution. The article concludes that Ragunan Zoo's conservation efforts have yielded positive results, contributing to preserving Indonesia's biodiversity while navigating the complexities of its dual role as a tourist attraction and conservation center.